2022
DOI: 10.1038/s41598-022-06771-x
|View full text |Cite
|
Sign up to set email alerts
|

Model based estimation of the SARS-CoV-2 immunization level in austria and consequences for herd immunity effects

Abstract: Several systemic factors indicate that worldwide herd immunity against COVID-19 will probably not be achieved in 2021. On the one hand, vaccination programs are limited by availability of doses and on the other hand, the number of people already infected is still too low to have a disease preventing impact and new emerging variants of the virus seem to partially neglect developed antibodies from previous infections. Nevertheless, by February 2021 after one year of observing high numbers of reported COVID-19 ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…As the incidence of seroconversion of 23.6–25.0% was markedly higher at that time point as predicted from the positive PCR tests, our data hint towards a significantly higher prevalence of SARS-CoV-2 positive people in this Austrian hotspot than officially recorded. This high level of undetected cases is in line with other reports from Austria [ 34 ].…”
Section: Resultssupporting
confidence: 92%
“…As the incidence of seroconversion of 23.6–25.0% was markedly higher at that time point as predicted from the positive PCR tests, our data hint towards a significantly higher prevalence of SARS-CoV-2 positive people in this Austrian hotspot than officially recorded. This high level of undetected cases is in line with other reports from Austria [ 34 ].…”
Section: Resultssupporting
confidence: 92%
“…The results of that study showed that countries with high incidences and death rates within the first wave had comparably low incidences and death rates within the second wave and vice versa [3]. In agreement with the idea of silent immunization due to unnoticed viral spreading, it was shown that previous infections reduced SARS-CoV-2 reproduction number and incidence in Austria [36].…”
Section: Discussionsupporting
confidence: 66%
“…However, the nature and setting of superspreading events is still an area of active research, cf., e.g., [ 37 , 38 ] and will take years to be fully understood [ 39 ]. Agent-based models (ABMs) have been used by many authors since they model infection dynamics in a natural way [ 40 48 ]. Another ABM based on a traffic simulation and mobile phone data was proposed by [ 49 ] and [ 50 , 51 ] presented agent-based models which build upon a predefined contact networks.…”
Section: Introductionmentioning
confidence: 99%